Adaptive-Fuzzy Controller Based Shunt Active Filter for Power Line Conditioners - Karuppanan PitchaiVijaya; KamalaKanta Mahapatra (Universitas Ahmad Dahlan, 2011)
This paper presents a novel Fuzzy Logic Controller (FLC) in conjunction with Phase Locked Loop (PLL) based shunt active filter for Power Line Conditioners (PLCs) to improve the power quality in the distribution system. The active filter is implemented with current controlled Voltage Source Inverter (VSI) for compensating current harmonics and reactive power at the point of common coupling. The VSI gate control switching pulses are derived from proposed Adaptive-Fuzzy-Hysteresis Current Controller (HCC) and this method calculates the hysteresis bandwidth effectively using fuzzy logic. The bandwidth can be adjusted based on compensation current variation, which is used to optimize the required switching frequency and improves active filter substantially. These shunt active power filter system is investigated and verified under steady and transient-state with non-linear load conditions. This shunt active filter is in compliance with IEEE 519 and IEC 61000-3 recommended harmonic standards.